Analysis of the Qur'an Surah At-Talaq Verse 12: Allah's Knowledge is Above All Knowledge - Eep Sulthoni (Aslama: Journal of Islamic Studies, 2024)
The purpose of this writing is to display the great power of God and it is unmatched by all creatures. The background of this writing is to inform all Muslims and mankind that God's knowledge and God's power are very great and that we should never oppose God that God's Wrath will always come when we oppose God's Teachings. That in this day and age, many people are opposed to God's authority and do not fear God and even do not know about God's existence. In this paper it is very important to be used as a reference in everyday life that the human race should not brag about itself until it claims to be great. The author also explains about the power of God in various interpretations by experts who understand correctly about the knowledge of God.